Implementasi Metode Supply Chain Operation Reference (SCOR) dan Analythical Hierarchy Process (AHP) Dalam Pengukuran Performansi Supply Chain Pada Koperasi X - Purwanti Purwanti; Nila Wati; Dinda Oe Mardy; Suseno Suseno (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
Supply Chain Management is a concept or mechanism to increase the total productivity of the company in the supply chain through optimizing the time, location and quantity flow of materials from raw materials to semi-finished products and finished products. The measurement design framework is prepared based on the functions or scope in the Supply Chain which refers to the Supply Chain Operation Reference (SCOR) such as: Plan, Source, Make, Deliver, and Return, with a performance measurement system consisting of aspects of Reliability, Responsiveness, Flexibility, Cost and Asset. Research on the measurement of Supply Chain performance was conducted at the Koperasi X dairy business entity. By taking these measurements, it is hoped that business entities can find out what scope must be improved. By using the Analytical Hierarchy Process (AHP) calculation, the performance value is 67.53. this figure indicates that the Supply Chain performance is sufficient. Based on the analysis of each scope, it is known that the scope with the lowest final score is Make, which is 53.25. the proposed improvement steps to improve the shortcomings of each in the scope are adding product variations, procurement automation, sustainable technology utilization, and improving relationship with supplier. It is expected that these improvements can be implemented gradually for maximum business entity development.